Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

5-(49/1-5)*2+9-3
what does this equal?


Sagot :

Answer:

the answer is -77 I just looked it up

Answer:
-71
Explaining:
5 - (49/1 -5) x2 + 9 - 3
The given expression is solved by using BODMAS rule which means the given expression will be solved in order of: Brackets, of, division, multiplication, addition, and subtraction.
= 5 - (49 -5) x2 + 9 - 3
= 5 - 44 x2 + 9 - 3
= 5 - 88 + 99 - 3
= 5 + 9 - 88 - 3
= 14 - 91
= - 71